NEW VARIABLE STARS IN THE FIELD OF 66 OPH ON DIGITIZED MOSCOW PLATES - Samus, N. N.; Antipin, S. V.; Kolesnikova, D. M.; Sat, L. A.; Sokolovsky, K. V. (Одеські астрономічні публікації, 2010)
Regular photographic observations at the Moscow Observatory began in 1895. The archive of direct and spectroscopic sky photographs kept at the Sternberg Astronomical Institute (SAI) currently contains more than 60000 photographs. The most important part of the Moscow plate stacks are about 22500 direct sky photographs acquired in 1948–1996 with a 40-cm astrograph, at different sites in Crimea and near Moscow (currently in Nauchny, Crimea). The size of its plates is 30 x 30 cm, corresponding to a 10° x 10° sky field. The limiting magnitude is 17.5m for good-quality plates.